R programming LiveLessons fundamentals to advanced - Lander, Jared P.; Safari eBooks ([Indianapolis, Ind.?] : Addison-Wesley : Pearson, 2014)
"R Programming LiveLessons: Fundamentals to Advanced is a tour through the most important parts of R, the statistical programming language, from the very basics to complex modeling. It covers reading data, programming basics, visualization, data munging, regression, classification, clustering, modern machine learning and more. Data scientist, Columbia University adjunct Professor, author and organizer of the New York Open Statistical Programming meetup Jared P. Lander presents the 20 percent of R functionality to accomplish 80 percent of most statistics needs. This video is based on the material in R for Everyone and is a condensed version of the course Mr. Lander teaches at Columbia. You start with simply installing R and setting up a productive work environment. You then learn the basics of data and programming using these skills to munge and prepare data for analysis. You then learn visualization, modeling and predicting and close with generating reports and websites and building R packages."--Resource description page.
Presenter, Jared Lander.
Title from title screen (viewed Jan. 21, 2014).
Keywords: R (Computer program language); Electronic books